New contours of the Arab-Israeli conflict (regional aspect) - D. A. Mirgorod (Современная наука и инновации, 2024)
One of the main determinants of the Middle Eastern system of international relations is the Arab-Israeli conflict. Its significance for the region has long been determined by the involvement of almost all regional and leading global actors in it. At the same time, over the past two decades, the ArabIsraeli conflict has experienced rescaling and a certain de-internationalization. The shift in foreign policy priorities of a number of Arab states, the signing of the Abraham Accords, the normalization of IranianSaudi relations, as well as the global context have shifted the issue of Palestine from the list of priority problems in the Middle East. In this regard, the next round of confrontation between Israel and Palestine somewhat falls out of the logic of regional development and has distinctive characteristics, especially taking into account the updated regional and global realities. Based on this, the purpose of this article is to identify the features of the current Palestinian-Israeli escalation of its regional and global projection.